Perancangan dan Implementasi Aplikasi Mobile BookMap Berbasis Android - Muhamad Alda; Aulia Alsaf Salsabilla; Farhanuddin Farhanuddin; M. Raihan Ath-Thoriq; RA. Ghina Zahidah (Journal of Information System Research (JOSH), 2025)
In the digital era, e-books have become a popular choice due to their high accessibility and portability. However, many users face challenges in finding book-reading applications that align with their preferences. To address this issue, this study developed BookMap, an Android-based book reading application equipped with features such as bookmarking, night mode, text search, and book collection management. The application was developed using the waterfall method, which includes stages of requirement analysis, design, implementation, and testing. The Kodular platform was utilized to streamline the application development process without requiring extensive technical programming knowledge. The results show that BookMap provides a comfortable and flexible reading experience, supported by personalization features such as digital bookshelf organization and night mode. Black box testing confirmed that all features functioned as intended. This application not only facilitates access to digital literature but also contributes to promoting reading interest and digital literacy in society. With its various advantages, BookMap is expected to serve as an innovative solution to support modern reading needs anytime and anywhere.